FOCAD loss impacts microtubule assembly, G2/M progression and patient survival in astrocytic gliomas - Brand, Frank; Förster, Alisa; Christians, Anne; Bucher, Martin; Thomé, Carina M.; Raab, Marc-Steffen; Westphal, Manfred; Pietsch, Torsten; Deimling, Andreas von; Reifenberger, Guido; Claus, Peter; Hentschel, Bettina; et al. (Acta neuropathologica, 2020)
In search of novel genes associated with glioma pathogenesis, we have previously shown frequent deletions of the KIAA1797/FOCAD gene in malignant gliomas, and a tumor suppressor function of the encoded focadhesin impacting proliferation and migration of glioma cells in vitro and in vivo. Here, we examined an association of reduced FOCAD gene copy number with overall survival of patients with astrocytic gliomas, and addressed the molecular mechanisms that govern the suppressive effect of focadhesin on glioma growth.